2020
DOI: 10.1101/2020.07.09.196154
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AMPA receptor anchoring at CA1 synapses is determined by an interplay of N-terminal domain and TARP γ8 interactions

Abstract: AMPA receptor (AMPAR) abundance and positioning at excitatory synapses regulates the strength of transmission. Changes in AMPAR localisation can enact synaptic plasticity, allowing long-term information storage, and is therefore tightly controlled. Multiple mechanisms regulating AMPAR synaptic anchoring have been described, but with limited coherence or comparison between reports, our understanding of this process is unclear. Here, combining synaptic recordings and super-resolution imaging, we compare … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 78 publications
2
3
0
Order By: Relevance
“…In this study, we observed that overexpression of GluA1ΔATD fails to change the synaptic rectification index in CA1 neurons, suggesting that the ATD of GluA1 is necessary for synaptic targeting, in line with the results obtained in hippocampal slice cultures (20,21). More recently, a study presented on the bio-Rxiv shows that, although GluA1ΔATD fails to rescue synaptic function, it does target at the PSD, implying that it may have different nanocluster properties compared to GluA1 (32). We also observed that GluA1 A2-ATD can mediate synaptic transmission, consistent with a previous study in slice cultures (21), indicating that an ATD is required for GluA1 to efficiently localize at the postsynaptic membrane.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this study, we observed that overexpression of GluA1ΔATD fails to change the synaptic rectification index in CA1 neurons, suggesting that the ATD of GluA1 is necessary for synaptic targeting, in line with the results obtained in hippocampal slice cultures (20,21). More recently, a study presented on the bio-Rxiv shows that, although GluA1ΔATD fails to rescue synaptic function, it does target at the PSD, implying that it may have different nanocluster properties compared to GluA1 (32). We also observed that GluA1 A2-ATD can mediate synaptic transmission, consistent with a previous study in slice cultures (21), indicating that an ATD is required for GluA1 to efficiently localize at the postsynaptic membrane.…”
Section: Discussionsupporting
confidence: 88%
“…However, the domains of AMPARs that mediate the interactions with those proteins have not yet been determined. Our findings of the GluA1 ATD-interacting protein Np65 and the demonstration of this interaction in mediating LTP maintenance, together with recent works (20,21,32), highlight the importance of the ATDs in AMPARs' synaptic anchoring during LTP.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Based on recent findings from us and others ( Díaz-Alonso et al, 2017 ; Sheng et al, 2018 ; Watson et al, 2017 ; Watson et al, 2020 ; Zeng et al, 2019 ), we propose that constitutive and activity-dependent AMPAR trafficking has two essential requirements. On one hand, the multivalent interaction between transmembrane AMPAR regulatory proteins (TARPs) and PSD scaffolding proteins (the intracellular slot).…”
Section: Discussionmentioning
confidence: 80%
“…Based on recent findings from us and others (Diaz-Alonso et al, 2017;Sheng et al, 2018;Watson et al, 2017;Watson et al, 2020;Zeng et al, 2019), we propose that constitutive and activity-dependent AMPAR trafficking has two essential requirements.…”
Section: Resultsmentioning
confidence: 85%